Diarrhea associated with Clostridium difficile in the oncology clinic - I. A. Klyuchnikova; D. A. Popov; I. N. Petukhova; Z. V. Grigorievskaya; N. S. Bagirova; I. V. Tereshchenko; N. V. Dmitrieva (Журнал инфектологии)
Purpose of the study. To conduct typing of toxigenic strains of Clostridium difficile, obtained from oncological patients who are in hospital.Material and Methods. The study included 130 patients with Clostridium difficile – associated diarrhea. First, the presence of toxins A+B+ in the feces was determined by enzyme immunoassay on an automatic miniVidas analyzer from BioMieux SA (France). For screening using real-time PCR, 26 toxigenic Clostridium difficile were selected. For the study used the system GeneXpert company «Cepheid» (Sweden).Results. Of the 1287 patients with diarrhea who were treated in an oncologic hospital, 130 (10,1%) tested positive for toxin A+B+ Clostridium difficile. For the study using real-time PCR, 26 samples were taken. The average age of patients is 57 years. 10 (38,5%) toxigenic strains were identified as hypervirulent ribotype. 7/10 strains were isolated for 3 consecutive month. The average age of patients with hypervirulent strains was 45 years. Patients participating in the study, in most cases were from the surgical departments – 61,5%, from the therapeutic – 34,7%.Conclusion. The study showed that the prevalence of Clostridium difficile infection in our clinic is lower than in other countries. Although hypervirulent strains accounted for 1/3 of all typed Clostridium difficile, special attention should be paid to them. Delayed diagnosis, delay in the onset of specific therapy in cancer patients can lead to a deterioration in the quality of life and in some cases be fatal. PCR diagnostics can determine the hypervirulent ribotype and carry out epidemiological measures aimed at preventing local outbreaks in the hospital.